Mercy Street : [large type] a novel - Haigh, Jennifer, 1968- (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"For almost a decade, Claudia has counseled patients at Mercy Street, a clinic in the heart of the city. The work is consuming, the unending dramas of women in crisis. For its patients, Mercy Street offers more than health care; for many, it is a second chance. But outside the clinic, the reality is different. Anonymous threats are frequent. A small, determined group of anti-abortion demonstrators appears each morning at its door. As the protests intensify, fear creeps into Claudia's days, a humming anxiety she manages with frequent visits to Timmy, an affable pot dealer in the midst of his own existential crisis. At Timmy's, she encounters a random assortment of customers, including Anthony, a lost soul who spends most of his life online, chatting with the mysterious Excelsior11--the screenname of Victor Prine, an anti-abortion crusader who has set his sights on Mercy Street and is ready to risk it all for his beliefs" -- Amazon.com.